Nanoapproaches to Modifying Epigenetics of Epithelial Mesenchymal Transition for Treatment of Pulmonary Fibrosis - Skibba, Melissa; Drelich, Adam; Poellmann, Michael; Hong, Seungpyo; Brasier, Allan R. (Frontiers in Pharmacology, 2020)
Idiopathic Pulmonary Fibrosis is a chronically progressive interstitial lung that affects over 3 M people worldwide and rising in incidence. With a median survival of 2-3 years, IPF is consequently associated with high morbidity, mortality, and healthcare burden. Although two antifibrotic therapies, pirfenidone and nintedanib, are approved for human use, these agents reduce the rate of decline of pulmonary function but are not curative and do not reverse established fibrosis. In this review, we discuss the prevailing epithelial injury hypothesis, wherein pathogenic airway epithelial cell-state changes known as Epithelial Mesenchymal Transition (EMT) promotes the expansion of myofibroblast populations. Myofibroblasts are principal components of extracellular matrix production that result in airspace loss and mortality. We review the epigenetic transition driving EMT, a process produced by changes in histone acetylation regulating mesenchymal gene expression programs. This mechanistic work has focused on the central role of BRD4 in mediating EMT and myofibroblast transition and initial preclinical work has provided evidence of efficacy. We then focus on the state of nanomedicine formulations for inhalable delivery in the treatment of pulmonary diseases, including liposomes and polymeric nanoparticles. These agents provide controlled release for enhanced therapeutic efficacy while reducing systemic toxicity. Nanoparticle-based approaches for pulmonary delivery offer substantial promise to modify epigenetic regulators of EMT and advance treatments for IPF.